The Role of Painting in Developing Students’ Visual Literacy and Creative Skills” - Sohibova Zuhroxon Akmal qizi (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Abstract: This article examines the significance of painting in fostering students’ visual literacy and creative skills. It highlights pedagogical strategies, interactive learning methods, and the use of modern technologies to enhance students’ aesthetic perception and artistic expression. The study emphasizes the importance of both individual and collaborative painting activities in higher education.